Economic Factors Affecting Gold Prices in Lao PDR - XAYSONGKHAM, Anouluck; SOMSAMONE , Vilayphon; XIOGTOUA, Tongvang (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This research provides an empirical analysis of the macroeconomic determinants of domestic gold prices (GPL) in the Lao People’s Democratic Republic (Lao P.D.R.) from April 2011 to April 2024. Using a high-frequency dataset of 157 monthly observations, the study examines the dynamic interactions between gold prices, exchange rate volatility (LAK/USD), and inflation dynamics (CPI). The theoretical framework is grounded in the Purchasing Power Parity (PPP) theory, utilizing advanced econometric procedures including the Augmented Dickey-Fuller (ADF) test, Johansen Cointegration, Vector Error Correction Model (VECM), and Granger Causality analysis. The empirical results confirm the existence of a stable, long-run equilibrium relationship among the variables. A key finding is the overwhelming dominance of the exchange rate as the primary driver of domestic gold prices; a depreciation of the Lao Kip leads to a significant and immediate increase in gold value. Interestingly, the study finds that domestic inflation is statistically insignificant in the long run, suggesting a "crowding-out" effect where currency volatility outweighs local price pressures due to the nation's high dependency on imports and dollarization. The VECM analysis reveals a "speed of adjustment" of approximately 8.8% per month, indicating a steady correction toward long-term equilibrium following market shocks. Furthermore, Granger Causality tests identify a unidirectional relationship where exchange rates and inflation "cause" gold price movements, confirming that gold in Laos acts as a reactive asset rather than an economic driver. These findings suggest that for the Bank of the Lao PDR, stabilizing the exchange rate is the most effective prerequisite for managing gold market volatility. For investors, the results underscore that gold serves as a critical strategic hedge against currency risk (LAK depreciation) rather than a mere inflation hedge. This study fills a vital gap in understanding commodity price discovery within small, open, and developing economies.